Agar Plate‐Based Screening Approach for the Identification of Enzyme‐Catalyzed Oxidations. Issue 11 (29th September 2022) - Kinner, Alina; Lütz, Stephan; Rosenthal, Katrin
Abstract: Biocatalytic oxidation reactions are in high demand. Among the applied enzymes, the heme‐thiolate enzyme subfamily of unspecific peroxygenases (UPOs), which relies on hydrogen peroxide as cosubstrate and oxidant, has generated great interest. Almost two decades after their first description, databases provide thousands of putative UPO sequences, but only a few enzymes have been characterized. To address this gap, efficient screening methods for the identification of novel UPOs are necessary. Here, a new screening strategy is presented based on solid cultivation of wild‐type fungi. The identification of a promising candidate strain highlights the applicability of this approach. Abstract : Unspecific peroxygenases (UPOs) naturally catalyzes a broad range of oxidative transformations by using hydrogen peroxide as electron acceptor. To identify new UPOs, a new screening strategy is presented based on solid cultivation of wild‐type fungi. The detection of a promising candidate strain highlighted the applicability of this approach.